Introduction to early childhood education - Essa, Eva L. (Unites States of America : Cengage Learning Asia Pte Ltd, 2014)
This book provides a comprehensive overview of early childhood education that is solidly based on current research and theories. Grounded in constructivist theory but also covering other perspectives, the book focuses on developmentally appropriate practices for infants and toddlers, preschoolers, early elementary schoolchildren, and children with disabilities. The majority of the text examines curriculum and the fostering of creativity as well as physical, cognitive, language, and social development--every facet of early childhood education is examined and explained This edition has been extensively revised and includes standards (both DAP and NAEYC) and accountability in the field of early childhood education, an expanded emphasis on working with children from diverse backgrounds, the latest brain-based research, and discussions of the role of families and forms of parent communication. With a strong emphasis on defining the components of high-quality early childhood programs, along with completely updated references, examples from practitioners, and new video offerings, this book is the most comprehensive resource available.
Part I. The What of Early Childhood Education -- Part II. The Who of Early Childhood Education -- Part III. The Why of Early Childhood Education -- Part IV. The Where of Early Childhood Education -- Part V. The How of Early Childhood Education - Curriculum -- Part VI. The How of Early Childhood Education - Guidance
Includes bibliographical references and index.
Keywords: EARLY CHILDHOOD EDUCATION